Testing the Validity of the Solow Growth Model: Empirical Evidence from Cross-Country Panel Data - Nkalu, Chigozie Nelson; Edeme, Richardson Kojo; Chukwuma, Queen O. (American Economic & Social Review, 2018)
This study seeks to test for the validity of the Solow growth model using cross-country panel data. Panel OLS analysis was adopted following an extensive review of recent and related literature with output-side of the real GDP as the dependent variable with other variables like population, capital stock and employment as the independent. However, population and capital stock are positively impacting the output with statistically significant value, while employment is not an important variable in the model even though it exhibits a negative and statistically significant effect to the output. In conclusion, the estimation result conforms the postulations of the basic Solow and augmented Solow growth model thereby validating the Solow model across-countries.